Causal Relationship Between Information Perception and Preventive Behaviors of COVID-19 Among Working Age People in Bangkok and Metropolitan Area, Thailand - Thanuttha Suwannakas; Vipakorn Vadhanasin; Sasipimol Prapinpongsakorn (Journal of Information Science Theory and Practice)
This study aims to examine the causal relationship between information perception and preventive behaviors regarding COVID-19 among working-age people in Bangkok and the metropolitan area of Thailand. The study investigated how information exposure, interpretation, and retention influence hygiene practices, virus spread prevention, health maintenance, and digital lifestyle adaptations among working-age individuals. Employing quantitative research methods, the sample group consisted of 421 working-age people in Bangkok and the metropolitan area. Data collection was conducted using a questionnaire. Analysis involved descriptive statistics, confirmatory factor analysis, and structural equation modeling. The results showed that the measurement model was well fitted to the empirical data. The findings reveal a significant correlation between information perception and the implementation of preventive measures among the working-age population in Bangkok, highlighting the pivotal role of accurate and effective information dissemination in influencing public behavior, especially now that COVID-19 has become a more manageable aspect of everyday life.